2000
DOI: 10.1161/01.cir.101.6.598
|View full text |Cite
|
Sign up to set email alerts
|

Extent and Direction of Arterial Remodeling in Stable Versus Unstable Coronary Syndromes

Abstract: Positive remodeling and larger plaque areas were associated with unstable clinical presentation, whereas negative remodeling was more common in patients with stable clinical presentation. This association between the extent of remodeling and clinical presentation may reflect a greater tendency of plaques with positive remodeling to cause unstable coronary syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
346
3
11

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 689 publications
(385 citation statements)
references
References 38 publications
25
346
3
11
Order By: Relevance
“…Consequently, early-stages of coronary atherosclerosis are angiographically undetectable, or underestimated when compared to postmortem pathological studies 21 . While positively remodeled lesions may have minimal stenotic effect, these plaques have been shown to be significantly associated with acute coronary syndromes 22,23 . Lumen imaging is also limited when long segments are diffusely affected by atherosclerotic changes, because the detection of angiographic stenosis relies on a comparison to a normal reference site 24 .…”
Section: Atherosclerosis Imaging and Luminal Stenosismentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, early-stages of coronary atherosclerosis are angiographically undetectable, or underestimated when compared to postmortem pathological studies 21 . While positively remodeled lesions may have minimal stenotic effect, these plaques have been shown to be significantly associated with acute coronary syndromes 22,23 . Lumen imaging is also limited when long segments are diffusely affected by atherosclerotic changes, because the detection of angiographic stenosis relies on a comparison to a normal reference site 24 .…”
Section: Atherosclerosis Imaging and Luminal Stenosismentioning
confidence: 99%
“…Initial description of plaque morphology focused on culprit lesions in patients presenting with acute or stable coronary syndromes 93,94 . Based on these studies, a prospective intravascular ultrasound study hypothesized that certain features would be associated with the development of acute coronary syndromes during follow-up 95 .…”
Section: Plaque Composition With Ivusmentioning
confidence: 99%
“…However, more recent angiographic data reveal that acute cardiovascular events do not necessarily correlate with the extent of obstructive coronary artery lesions. 1,2 Furthermore, interventions that improve outcome may have only a minimal impact on severity of obstruction yet profoundly modulate plaque echogenicity. 2,3 Such observations suggest that the atherosclerotic plaque is not merely a static repository for lipid waste but rather a dynamic lesion that can be remodeled in ways that influence the likelihood of plaque instability and acute vascular events.…”
mentioning
confidence: 99%
“…However, some previous reports with multislice CTCA have shown that the whole area of noncalcified plaque and the remodeling index at the culprit lesion were greater in ACS patients than in non-ACS patients, although the lumen stenotic ratio did not differ between ACS patients and non-ACS patients. 13,21,28,29) This may be mainly explained by differences in patient backgrounds. Patients with myocardial infarction (MI) were not included in the present study, whereas the previous reports did include MI patients.…”
Section: Discussionmentioning
confidence: 99%